Budgets: How They Are Planned, Prepared, and Managed - Rajiv Chandawarkar, MD, MBA; Prakash Nadkarni, MD; Elizabeth Barmash, MD; Peter Krasniak, MD; Allison Capek, PAC; Kathleen Casey, PAC (Plastic and Reconstructive Surgery, Global Open, 2024)
Background:. Budget planning and execution is as difficult as it is vital to any practice, whether academic, private, or group. Well-planned and executed budgets are a source of revenue and growth that fuels the practice for the next cycle. Conversely, poorly planned budget is disastrous, and a badly executed one invariably leads to unrecoverable losses. Many clinicians, especially those in academic centers, are not involved in budget-planning preparation and yet are held accountable for their yearly performance in relation to the budget. Methods:. Key processes for budget planning and their significance are identified. Integrating these steps with the needs of a clinical practice, a stepwise method is described for both clinicians and administrators to work together to plan, prepare, and manage budgets. Results:. Relevant examples of how budgets affect clinical workflow and common pitfalls of budget planning and mitigation methods are identified. A simplified systematic approach allows for a streamlined, smooth budget-planning process that involves faculty and staff, which holds them accountable for the year-long performance of the entire clinical team. Conclusions:. A systematic proactive approach to budget-planning, preparation, and management provides a financial direction to the department; tracks performance; allows growth; and provides the flexibility to stay on track, change course, or reassign resources.